2021
DOI: 10.1371/journal.pone.0246216
|View full text |Cite
|
Sign up to set email alerts
|

Selection for feed efficiency elicits different postprandial plasma metabolite profiles in response to poor hygiene of housing conditions in growing pigs

Abstract: This study was conducted to compare postprandial plasma concentrations of insulin, energy-related metabolites, and amino acids measured after a 6-week challenge consisting of exposure to good or poor hygiene of housing conditions of 24 growing pigs divergently selected for low-RFI (LRFI) and high-RFI (HRFI). Blood indicators of immune responses were assessed from samples collected before 0 (W0), and 3 (W3), and 6 weeks (W6) after pigs transfer to their respective hygiene of housing conditions. Plasma haptoglob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…During the post-weaning period, pigs fed AAP diet had lower plasma haptoglobin concentrations, a trend to lower values of dROM and ISO, and greater concentrations of vitamins E and A compared to CNT pigs. Haptoglobin is a major acute phase protein in pigs and an increase in its plasma concentration is an indicator of inflammation and/or infection [ 13 ]. Weaning is known to increase the concentration of haptoglobin in the plasma [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the post-weaning period, pigs fed AAP diet had lower plasma haptoglobin concentrations, a trend to lower values of dROM and ISO, and greater concentrations of vitamins E and A compared to CNT pigs. Haptoglobin is a major acute phase protein in pigs and an increase in its plasma concentration is an indicator of inflammation and/or infection [ 13 ]. Weaning is known to increase the concentration of haptoglobin in the plasma [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…All pigs were fed the same standard diet formulated to meet the nutritional requirements of growing pigs (9.47 MJ of net energy/kg, starch 44.2%; fat 3.1%; crude protein 15.3% and 8.3 g of standardized ileal digestible lysine (SID Lys), SID Lys/kg). The model of good and poor hygiene condition study was described in detail in previous studies [ 13 , 28 ]. To summarize, poor housing conditions consisted of no cleaning nor sanitation of the room after a previous occupation by non-experimental pigs, whereas for good hygiene conditions, the room was cleaned daily, in addition to the application of optimal aeration rate and temperature and strict biosecurity precautions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the inclusion levels of ingredients are calculated to obtain optimal animal performance, which means an efficient use of the agricultural land to produce animal protein. Based on a previous study, pigs with increased insulin plasma levels have an improved use of amino acids such as lysine, tryptophan, and arginine [ 15 ]. Furthermore, insulin allows the use of amino acids for muscle protein synthesis [ 16 ], suggesting that it will support the growth of pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Feed efficiency in piglets correlates with specific microbiota and with bacterialrelated metabolites in intestine (Wang et al, 2021). Based on metabolic research in the postprandial period in piglets, it has been shown that piglets with lower residual feed intake grow much better in poor hygienic conditions, due to better use of amino acids and better postprandial glucose and insulin dynamics (Zem Fraga et al, 2021). In a study by Kabalin et al (2017) compared metabolic parameters in piglets of low and high birth weight.…”
Section: Introductionmentioning
confidence: 99%